Pathological and Immunohistochemical Assessment of Salmonellatyphimurium Pathogenicity During Oral Experimental Infection in Mice (Medico Legal Update, 2021)
Salmonella typhimurium is a Gram-negative zoonotic bacterium which causes a wide range of illnesses to both humans and animals. The aim of this research is to study the pathogenicity of S. typhimurium in vivo. A total of 40 adult white BALB/c mice were divided into 5 groups (8 animals each). Four groups were orally dosed by viable S. typhimurium (1 X 109 cfu/ml) suspended in phosphate buffer saline (PBS) by a stomach tube, while the fifth group was given PBS orally only (control group). Four mice were killed at 7, 12, 24, 48 hours after giving the infective dose plus one mouse from the control group. In addition, sera were collected after 2 weeks from animals of each group to detect the titer of antibodies. The viability of S. typhimurium was checked by culturing on SS agar after mice death. Slides were prepared for histopathological examination (to assess the lesions) and immuno-histochemistry (to detect cytotoxic T cells in the affected organs). The results included bacterial isolation from duodenum, jejunum, ileum and liver which were positive from the infected groups. Histopathological examination showed hepatic granulomatous lesions with severe infiltration of mononuclear cells (MNCs) in the liver parenchyma and within small intestine. Finally, to detect cytotoxic T cells in the slides, immunohistochemistry showed presence of CD8 T cells in the hepatic cells. Titers of antibodies were measured by ELISA where IgG antibodies were detected. The conclusion of this study could be summarized by addressing the severity of infection after 12 hours of oral dosing in the stomach while severe lesions were seen in the liver after 48 hours of oral administration.